FAKTOR INTERNAL YANG BERPENGARUH TERHADAP KINERJA REKSADANA SYARIAH DI INDONESIA PERIODE 2014-20171) - Farah Faadilah; Puji Sucia Sukmaningrum (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
This study aims to determine the effect of fund size, expense ratio and turnover ratio. The data used in this research is the net asset value data and shariah mutual fund prospectus of 4 shariah equity funds for the period 2014-2017. This study describes using multiple linear regression test to prove the relationship between exogenous and endogenous variables. The result of the test shows that partially fund size and positive effect is not significant on the performance of Islamic stock mutual funds, the expense ratio has no significant negative effect on the performance of Islamic equity mutual funds, while the turnover ratio has a significant positive effect on the performance of sharia mutual funds. While simultaneously fund size, expense ratio and turnover ratio have a significant influence with the coefficient of determination of 25,06%% while the remaining 74,94%  influenced by other variables not included in this study.Keywords: Sharia Mutual Funds Performance, Turnover Ratio, Cash Flow, Expense RatioREFERENCES Baroroh, Ali. 2013. Analisis Multivariat dan Time Series dengan SPSS 21. Jakarta: PT Elex Media Komputindo. Bitomo, Habib & Harjum Muharam. 2016. Analisis Faktor-Faktor yang Mempengaruhi Kinerja Reksa Dana di Indonesia. Diponegoro Journal of Management, Vol. 5, No. 2, hlm. 1-14.Departemen Agama RI. 2009. Al-Qur’an dan Terjemahnya. Jakarta: Syaamil Quran.Data Produk Reksadana Syariah per Desember 2016 (www.ojk.go.id, diakses pada 6 April 2018).Statistik Reksadana Syariah. Perkembangan Reksadana Syariah per Desember 2016 (www.ojk.go.id, diakses 6 April 2018).Tandelilin, Eduardus. 2010. Portofolio dan Investasi: Teori dan Aplikasi. Yogyakarta: Kanisius.Sharpe, William F. 1981. Investments. USA: Prentice Hall.Yuliana, Indah . 2010 . Investasi Produk Keuangan Syariah . Malang : UIN Maliki Press www.dsnmui.or.id, diakses pada 28 Februari 2017.Liitequran, http://litequran.net  (diakses tanggal 15 febuari 2018)www.anggaran.depkeu.go.id (diakses pada 2 April 2018)